iPhone Application Sketch Book - Kaplan, Dean.; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
Think you have the next great iPhone app idea? The Apress iPhone Application Sketch Book is an essential tool for any aspiring iPhone developer. This sketch book makes it easy to centralize and organize your ideas, featuring 1.5x sized iPhone templates that include common elements such as the status bar, signal strength, and battery icons. Professionally printed on high-quality paper, it has a total of 150 gridded templates for you to draft ideas and doodle designs while providing ample room to make notes, and document the app name and screen name. This book is a must-have and an invaluable tool for bringing your next great iPhone app idea to life! Makes it easy to keep your design ideas organized in one central place. Includes 150 templates at 1.5x magnification for easy use, with plenty of room on the gridded page to jot notes and doodle designs. This professional notepad gives your design a finished look from which to share ideas with colleagues and clients.
Keywords: Computer science; Computer Science; Programming Techniques